PENGARUH KONSUMSI EKSTRAK KALDU AYAM TERHADAP PERTUMBUHAN TINGGI BADAN ANAK 12 - 48 BULAN - Pascoal, Meildy E.; Sahelangi, Olvie; Ranti, Irza Nanda (Poltekkes Kemenkes Bandung, 2023)
One intervention to prevent stunting in toddlers is to provide local foods that are highly nutritious. The study aimed to determine effect of consumption of chicken feet extract broth on height growth of children aged 12-48 months. The research design is a quasi-experimental design with a pre test-post test design. Sampling was carried out using simple random sampling and a sample of 30 was obtained. The research was carried out in May-June 2023 in Mopusi Village, Bolaang Mongondow. Comparing changes in toddlers' height before and after intervention using the Paired t-Test. Proximate test results of chicken feet broth extract moisture content 68.2%, ash content 0.44%, carbohydrate content 6.12, protein content 6.46%, fat content 18.72%, calcium content 314.25 mg/kg, phosphorus content 0.005 mg/kg, potassium content 262.20 mg/kg, iron content 4.78 mg/kg. The average height of children in the intervention group of chicken feet extracts broth flour pre-test 86.91 cm and post-test 88.44 cm with a difference of 1.53 cm and the control group pre test 88.84 cm and post-test 89.84 cm with a difference of 1.01 cm. The results showed that there was a significant difference in the pre post-test of giving chicken feet extract broth on children's height (p = 0.00 <0.05). The study conclude that giving Chicken Claw Broth Extract can increase children height. It is recommended to consult health professional before introducing chicken claw extract broth into a child's diet. Additionally, further research is needed to fully understand the long-term impacts and potential risks associated with these interventions.